REAKSI HARGA SAHAM, ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM ATAS PERISTIWA STOCK SPLIT (Studi pada Perusahaan-Perusahaan Go Public di BEI Periode 2011-2014) - Itsnaa Qurrotu A’yyunin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purposes of the research is to reveal the effect of stock price reaction, abnormal return, and trading volume activity on stock split announcement for go public companies listed in IDX during 2011 and 2014. The stock split was carried out based on trading range theory and signaling theory. This research used event study method to observe the average of stock price (measured by daily closing price), abnormal return and trading volume activity within five days pre and post event date. There were 31 companies which conducted stock split decision. This reasearch used secondary data retrived from IDX Corner. This research utilized paired sample t-test to compare means when the data had normal distribution or wilcoxon signed ranks test when the data had abnormal distribution. The results of these research show that there were differences in stock price, abnormal return and trading volume activity before and after stock split announcement. It indicated that the carried our stock split during the research period delivered a signal to the investors. Key words: stock split, stock price, abnormal return, trading volume activity, event study